Analysis of Lecturers Competency Performance Evaluation using Fuzzy Modeling - Nugroho, Jeffrey; Linawati, Lilik; Mahatma, Tundjung (International Journal of Active Learning, 2019)
In the Indonesian 2005 Law (UU No. 14 Tahun 2005) about Teachers and Lecturers there are four competencies that must be owned by a lecturer in carrying out the duties ?the Tridharma? namely pedagogic, personality, professional, and social competence. This research analyzes the evaluation results of lecturer's performance at the Faculty of Science and Mathematics using fuzzy modeling, employing the FIS Mamdani method.. The twelve aspects assessed in the questionnaire are grouped into four competencies with an assessment of 1 (not good), 2 (poor), 3 (good), and 4 (excellent). The average value of each aspect of each competency is used to derive the fuzzy value of each competency. The value of each competence is then used to get the final value of lecturer performance evaluation, to be back-processed into the crisp value which is translated through membership function. Based on the criteria set by the faculty, i.e. ?Poor?, ?Fair?, and ?Good?, the results show that the performance evaluation of all lecturers are "Fair" towards "Good", but when the assessment uses the average value, all lecturer have a ?Good? performance except one lecturer who shows ?Fair? performance.